Potensi Dan Penyebaran Terubusan Ulin (Eusideroxylon zwageri Teijsm. & Binn.) Di Taman Nasional Kubah, Sarawak - Karyati, Karyati; Ipor, Isa B.; Yusuf, Sharifah Mazenah Wan (Jurnal Magrobis, 2015)
Ironwood or Ulin (Eusideroxylon zwageri Teijsm. & Binn.) coppice are potential natural regeneration to preserve Ulin resouces. A survey of ironwood regeneration was conducted as long as Belian Trail in Kubah National Park, Sarawak, Malaysia. A total of 33 coppice-shoots were recorded on 22 Ulin stumps. There were 6 seedlings, 49 saplings, 23 poles, and one tree recorded surrounding the coppicing. They were found in Quadrant I (25), Quadrant II (27), Quadrant III (16), and Quadrant IV (9). Information about regeneration and coppicing pattern of Ulin are useful for forest management and conservation, due to availability of their high natural regeneration.Keywords: Distribution, regeneration, coppice, stump, ironwood.